log(x+2)=2*log(3)-log(2)

Дано

$$\log{\left (x + 2 \right )} = — \log{\left (2 \right )} + 2 \log{\left (3 \right )}$$
Подробное решение
Дано уравнение
$$\log{\left (x + 2 \right )} = — \log{\left (2 \right )} + 2 \log{\left (3 \right )}$$
$$\log{\left (x + 2 \right )} = — \log{\left (2 \right )} + 2 \log{\left (3 \right )}$$
Это уравнение вида:

log(v)=p

По определению log

v=e^p

тогда

-log(2) + 2*log(3)
——————
1
x + 2 = e

упрощаем
$$x + 2 = \frac{9}{2}$$
$$x = \frac{5}{2}$$

Ответ
Читайте также  9*x^3-15*x^2-32*x+6=0
$$x_{1} = \frac{5}{2}$$
Численный ответ

x1 = 2.50000000000000

1 Звезда2 Звезды3 Звезды4 Звезды5 Звезд (Пока оценок нет)
Загрузка...